Penokohan dalam Novel Lima Sekawan yang Melacak Jejak Rahasia Karya Enid Blyton - Jeverson Nawa Wanyi; Richard Oematan; Sanhedri Boimau (KAMPUS AKADEMIK PUBLISING, 2026)
The problem raised in this study is: How is the characterization in the novel